The Effect of Shellac as Coating Material on the Internal Quality of Chicken Eggs - Musa, Tariq N.; Ulaiwi, Wisam S.; Al-Hajo, Nadia N.A. (International Journal of Poultry Science, 2010)
The functional properties of foods can be preserved when they are coated with edible films, which are especially reduce the moisture loss and the transportation of O2 and CO2. The present research is conducted to study the effect of shellac as coating material and storage time on the internal quality of chicken eggs. 448 fresh chicken eggs were divided into 4 groups of treatments 0, 1, 3 and 5% shellac solutions and stored for 0, 10, 20 and 30 days at 40oC. There was a proportional relationship between the weight loss of eggs and the pH values of untreated eggs (control) during the storage time. A reverse relationship was appeared with coated chicken eggs. The Haugh unit (Hu) usually decrease with the time of storage, but this was limited with coated eggs. No bad changes were associated with internal quality of chicken eggs, so we recommend shellac solution as coating material.